2000
DOI: 10.1038/sj.ejhg.5200498
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the size of the deletion and clinical manifestation in Wolf-Hirschhorn syndrome: analysis of 13 patients with a de novo deletion

Abstract: We performed clinical, cytogenetic, and molecular analyses on 13 patients (8 females and 5 males, aged 6 months to 13 years) with Wolf-Hirschhorn syndrome due to de novo deletions of chromosome 4p. All patients presented with the typical facial gestalt, microcephaly, and profound mental retardation. Other clinical signs were low birth weight (10/13; 77%), postnatal short stature (8/12; 66%), muscular hypotonia (12/13; 92%), seizures (11/13; 85%), congenital heart defects (4/13; 31%), colobomata of iris (4/12; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 33 publications
6
67
0
4
Order By: Relevance
“…Wieczorek and co-workers 14 previously reported a correlation in WHS between postnatal head circumference and deletion size. The original aim of this study was to analyse the effects of deletion size on facial morphology in WHS.…”
Section: Wolf-hirschhorn Syndrome (Whs; Omim 194190) Is a Contiguous mentioning
confidence: 91%
See 1 more Smart Citation
“…Wieczorek and co-workers 14 previously reported a correlation in WHS between postnatal head circumference and deletion size. The original aim of this study was to analyse the effects of deletion size on facial morphology in WHS.…”
Section: Wolf-hirschhorn Syndrome (Whs; Omim 194190) Is a Contiguous mentioning
confidence: 91%
“…13 There is considerable variation in the phenotypic spectrum, and, more recently, a correlation with the size of the deletion has been recognized; children with submicroscopic deletions within 4p16.3 tend to have a milder phenotype. 14,15 Some patients with microdeletions within 4p16.3 were initially reported as having Pitt-Rogers-Danks syndrome, now considered to be within, and at the milder end of, the WHS spectrum. 16,17 We use small and large, respectively, to refer to a terminal deletion with a break point within 4p16.3, a deletion size of about 3.1 Mb or less, and one with a break point more proximal than 4p16.…”
Section: Wolf-hirschhorn Syndrome (Whs; Omim 194190) Is a Contiguous mentioning
confidence: 99%
“…Death occurs more frequently in patients with larger deletions. It had been proven that the larger deletion, the more severe congenital deformities one presents [1,12,17]. The other congenital defects include muscle hypotonia and urinary tract malformations (such as renal agenesis, oligomeganephronia, bladder exstrophy, cystic dysplasia/hypoplasia and obstructive uropathy) [18].…”
Section: Congenital Defectsmentioning
confidence: 99%
“…It occurs two times more frequently in females [11][12][13]. The more chromosomal material is missing, the larger expression of WHS is observed in patients [7].…”
mentioning
confidence: 99%
“…Genotype-phenotype correlation studies have shown a relationship between deletion size and severity of clinical presentation. [6][7][8] Of patients meeting the minimal diagnostic criteria, 9 the smallest terminal deletion identified was B1.9 Mb, 1, 9,10 suggesting that genes within this interval of 4p16.3 are responsible for the core features of WHS. 8,11 Beyond this region, the loss of additional critical genes appears to be responsible for variably present features, such as congenital malformations or hearing loss.…”
Section: Introductionmentioning
confidence: 99%